PP21 Hangings attended by emergency medical services: a scoping review. Issue 9 (19th August 2021) - Shaw, Gary; Thompson, Lee; McClelland, Graham
Abstract : Background: In the United Kingdom (UK) there were 6, 507 deaths by suicide in 2018 with hanging being the most common method. Hanging will normally result in emergency medical services (EMS) being called and may result in resuscitation being attempted. The lead author identified an increasing trend in hanging cases in the NHS Ambulance service trauma audit, which were also reported in national data. The aim of this scoping review was to explore the literature around EMS attendance at hangings to inform further research and clinical practice. Methods: A five-stage scoping review method was used. Relevant studies were identified by searching MEDLINE, CINAHL, EMBASE and EMCARE with the help of the Library and Knowledge Service for NHS Ambulance Services in England (LKS). Grey literature and reference lists were also searched. Studies were included based on relevance to hangings attended by EMS. Data were tabulated and narratively synthesised. Results: Sixteen papers were included in the review. Australia was the most frequent source of studies (n=5, 31%). Most studies (n=11, 69%) were published in the past ten years. The median sample size was 53 (IQR 41-988, range 10-3981). All papers included varying levels of patient characteristics, EMS input and patient outcomes. Conclusion: Hanging is a highly lethal method of suicide that is increasingly used in the UK. This scoping review found that there is scarce literature focussed on hangings attended by EMS. Treatment of the hanging patient in cardiac arrest is described in many of the papers included. Hanging patients may benefit from the presence of specialist resources who can deliver interventions such as sedation and advanced airway management. The psychological impact of attending, or witnessing, hanging patients is an area that needs further consideration. Further research is needed to describe and improve EMS treatment of hangings.